Regulations and Reimbursement of Digital Therapeutics: A Review of Current Global Practices and Future Prospects - Dang, Amit; Dang, Dimple; Rane, Pawan (Applied Drug Research, Clinical Trials and Regulatory Affairs, 2021)
The ever-increasing use of digital technologies is rapidly changing the face of modern healthcare delivery. Healthcare systems are embracing digital health solutions to improve patient outcomes, enhance healthcare delivery, and reduce costs. Digital therapeutics (DTx) are now a popular category of digital health solutions aimed at preventing, managing, or treating medical disorders. These evidence-based technologies/products either complement a conventional therapy or are prescribed as stand-alone treatments for a range of conditions, including chronic diseases and mental health disorders. Many pharmaceutical companies and healthcare start-ups are developing DTx products for different health conditions. Despite similarities between DTx and conventional medicines, DTx products are not covered under reimbursement at present in many countries. There are no uniform regulations for DTx prescription and reimbursement. This review aims to analyse the current DTx scenario, particularly highlighting the regulatory aspect and reimbursement of DTx products globally.
Keywords: DTx review